The United States in the Indo-Pacific : Obama's Legacy and the Trump Transition - Oliver Turner; Inderjeet Parmar (Manchester University Press, 2020)
This electronic version has been made available under a Creative Commons (BY-NC-ND) open access license. This edited collection examines the political, economic and security legacies of former US President Barack Obama in Asia and the Pacific, following two terms in office between 2009 and 2017. In a region that has only become more vivid in the American political imagination since Obama left office, this volume interrogates the endurance of Obama's legacies in what is increasingly reimagined in Washington as the Indo-Pacific. Advancing our understanding of Obama's style, influence and impact throughout the region, this volume explores dimensions of US relations and interactions with key Indo-Pacific states including China, India, Japan, North Korea and Australia; multilateral institutions and organisations such the East Asia Summit and ASEAN; and salient issue areas such as regional security, politics and diplomacy, and the economy. How far has the Trump administration progressed in challenging or disrupting Obama's Pivot to Asia? What differences can we discern in the declared or effective US strategy towards Asia and to what extent has it radically shifted or displaced Obama-era legacies? Including contributions from high-profile scholars and policy practitioners such as Michael Mastanduno, Bruce Cumings, Maryanne Kelton, Robert Sutter and Sumit Ganguly, contributors examine these questions at the halfway point of the 2017–21 Presidency of Donald Trump, as his administration opens a new and potentially divergent chapter of American internationalism.An electronic edition of this book is freely available under a Creative Commons (CC BY-NC-ND) licence.